Evaluasi Sistem Produksi dan Prediksi Umur Sumur Natural Flow dengan Tren Historis Tubing Head Pressure dan Decline Curve Analysis: Studi Kasus Sumur Jz-22 Sangatta Field - Nania Salsabila; Herlina Imeli Awan; Andi Atsiilah Besse Combo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
A decline in reservoir pressure in a natural flow well reduces the well’s ability to flow fluid naturally, necessitating an evaluation of the production system and a prediction of the well’s lifespan. This study was conducted on Well JZ-22 in the Sangatta Field using actual production data from August 12, 2025, employing Nodal analysis, System Analysis, Tubing head pressure (THP) trend analysis, and Decline curve analysis (DCA). The matching results indicate a production rate of 20.57 bfpd with a model THP of 15 psig and a reservoir pressure of 110 psia. Future IPR analysis indicates that the well will no longer be able to flow naturally at a reservoir pressure of 57 psia with a production rate of 0.85 STB/d. Predictions based on the THP trend indicate that the well will stop flowing on August 26, 2025, while the DCA method estimates that it will continue until January 3, 2026. The research results indicate that Well JZ-22 is in the final phase of natural flow, necessitating intervention planning such as the installation of an artificial lift system.